Trump’s Performance on Instagram: A Study of the Strategies for Constructing, Identities, Representations and Legitimacies during the Electoral Campaign of the US Elections - Díaz-Maroto Oro, Ramiro; Caffarel Rodríguez, Bárbara (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
In a context determined by the action frameworks of the discursive power of political actors constituted by technology, performativity transcends dichotomous schemes to understand power relations. This study seeks to find out if the strategies used by Trump on Instagram during the electoral campaign were effective in creating identities, representations and legitimacies. The result of the content analysis reflect how the creation of a specific political identity ends up becoming the articulation of a legitimized social power, transforming the symbol into an icon, a myth and definitively this, as concluded, into an effective power.